Resurrection and redemption a study in Paul's soteriology - Gaffin, Richard B. (Phillipsburg, NJ Presbyterian And Reformed, 1987)
Includes bibliographical references and indexes.
First edition entitled "The centrality of the resurrection", Grand Rapids, MI, Baker, c. 1978.
Keywords: Bible. N.T. Epistles of Paul -- theology; Resurrection -- biblical teaching; Salvation -- biblical teaching